N Terminal-Pro B Type Natriuretic Peptide (NT- PRO BNP) levels and severity of disease in elderly with heart failure - Erlina Marfianti; Ana Fauziyati; Barmawi Hisyam (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Heart failure is a major health problem in the world. It is associated with high morbidity and high mortality especially in elderly patients. Most studies reported using N terminal pro-B type natriuretic peptide (NT-proBNP) in diagnosis of heart failure, but about of these tests in determining classification of severity of heart failure in the elderly remain unclear.Objective: To determine the differences NT-pro BNP levels based on the severity of diease of heart failure in elderly patients.Methods: This is an observational study with cross sectional design. Subjects were patients with diagnosed heart failure and aged = 60 years. Patients were divided into two groups, mild and severe heart failure groups according to severity of heart failure in New York Heart Association (NYHA) class. The NT Pro-BNP levels were measured for all subjects in both groups. Data was analyzed with using unpaired t test and was considered significant if p <0.05.Results: This study involved 24 subjects, consisting of 2 gorups, there were mild heart failure groups (NYHA class I-II) and groups of patients with severe heart failure (NYHA III-IV). The mean age of the subjects was 64.50 ± 4.65 years with a minimum age of 60 years and a maximum of 78 years. The NT pro-BNP levels in the severe heart failure group (1.2587.58 ± 574.85 pg / ml) was higher than the mild heart failure group (867.83 ± 333.27 pg / ml), it was statistically significant with p = 0.040.Conclusion: The levels of NT-pro BNP serum in elderly patients with severe heart failure (NYHA III-IV) were significantly higher than in patients with mild heart failure (NYHA I-II).